Diagnostic Value of Measurements of Median Nerve Diameter at the Site of the Maximal Stenosis in Carpal Tunnel Syndrome - Fryźlewicz A; Rusin G; Rudnicki W; Ułamek-Kozioł M; Antczak J (International Journal of General Medicine)
Agnieszka Fryźlewicz,1 Gabriela Rusin,1 Wojciech Rudnicki,2 Marzena Ułamek-Kozioł,3 Jakub Antczak4 1Department of Neurology, University Hospital in Krakow, Cracow, Poland; 2Department of Radiology, University Hospital in Krakow, Cracow, Poland; 3Department of Neurology, Institute of Psychiatry and Neurology, Warsaw, Poland; 4Department of Neurology, Jagiellonian University Medical College, Krakow, PolandCorrespondence: Jakub Antczak, Department of Neurology, Jagiellonian University Medical College, ul. Jakubowskiego 2, Kraków, 30-688, Poland, Tel +48 12 400 25 50, Fax +48 12 400 25 67, Email jakub.antczak@uj.edu.plIntroduction: Ultrasonography is increasingly used to diagnose the carpal tunnel syndrome (CTS). Most frequently, the enlargement of the nerve cross-sectional area (CSA) at the tunnel inlet serves to confirm the diagnosis. Recent research has shown that the nerve diameter is decreased within the tunnel, when measured at the level of pisiforme or capitatum. The stenosis index (SI), which uses the ratio of the diameter of median nerve at the tunnel inlet to the diameter within the tunnel (SI diameter), was proposed as the diagnostic marker of CTS. In this study, we compared the diameter of the median nerve measured at the site of maximal stenosis (DMS) between patients with CTS and controls. Additionally, we investigated the diagnostic utility of the modified SI, which uses the ratio of CSA at the inlet to the diameter within the tunnel (SI CSA).Methods: Forty-eight patients (72 hands) with CTS and 18 asymptomatic controls (28 hands) underwent electrodiagnostic testing and ultrasonography.Results: CSA at the inlet was larger in patients, whereas DMS showed only trend towards being smaller in CTS. CTS was also associated with more distal localization of maximal stenosis. Both SI diameter and SI CSA were higher in patients, however the discriminative effect of SI CSA was stronger. SI diameter, SI CSA, CSA at the inlet and DMS correlated with the electrodiagnostic severity grade of CTS. The post-hoc analysis revealed that patients with moderate and severe electrodiagnostic grade of CTS have smaller DMS, whereas patients with mild CTS did not differ from controls.Conclusion: DMS seems to have only limited diagnostic potential in mild CTS, but it may be a marker of more advanced cases. CTS may be associated with the distal shift of DMS. SI CSA may have significant diagnostic potential in CTS.Plain Language Summary: Carpal tunnel syndrome is a frequent condition, where the median nerve is compressed within the wrist by surrounding anatomical structures. As a consequence, the pain and numbness of the wrist, hand and fingers (except the little finger) occur. Further symptoms include loss of grip strength and hand dexterity. Traditionally, diagnosis is supported by the nerve conduction study, a medical procedure which may be painful. A painless alternative is the ultrasonography, which usually visualizes the nerve enlargement close to the compression. Only recently, ultrasound equipment became advanced enough to visualize the compression itself (Anatomical structures surrounding the nerve within the tunnel make the transmission of the ultrasound-waves difficult). In consequence, a number of researchers attempted to measure the nerve at the compression site to improve the diagnosis. They used to measure the diameter of the compressed nerve at certain anatomical point (landmark), eg, the hamate bone. In this work, we investigated the diagnostic usefulness of the measurement of nerve diameter at the maximal compression. Obtained results revealed that measurement at this point may not be an efficient diagnostic method at least in the early stage of the disease. On the other hand, when we combined this measurement with traditional measurement of nerve enlargement close to compression, the diagnostic accuracy turned to be very efficient.Keywords: carpal tunnel syndrome, ultrasound, nerve stenosis, cross-sectional area, stenosis index